2020
DOI: 10.1111/myc.13170
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 1,3‐β‐d‐glucan by Wako β‐glucan assay for rapid exclusion of invasive fungal infections in critical patients: A diagnostic test accuracy study

Abstract: Summary Objectives Rapid and reliable exclusion of invasive fungal infections (IFI) by markers able to avoid unnecessary empirical antifungal treatment is still a critical unmet clinical need. We investigated the diagnostic performance of a newly available β‐d‐Glucan (BDG) quantification assay, focusing on the optimisation of the BDG cut‐off values for IFI exclusion. Methods BDG results by Wako β‐glucan assay (lower limit of detection [LLOD] = 2.16 pg/mL, positivity ≥ 11 pg/mL) on two consecutive serum samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A 5 pg/mL cutoff was optimum for the diagnosis of IFD using the Fujifilm Wako assay with a sensitivity of 79.4% and specificity of 88.3%. Previously, a study by Cento et al revealed that the single quantification of serum BDG using the Fujifilm Wako assay had a sensitivity of 56%, specificity of 87%, NPV of 85%, and PPV of 59% at the cutoff of 11 pg/mL in critically ill ICU and non-ICU patients [ 10 ]. Lowering the cutoff to 7.7 pg/mL, the sensitivity, specificity, NPV, and PPV were 56%, 87%, 85%, and 59%, respectively, similar to our findings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5 pg/mL cutoff was optimum for the diagnosis of IFD using the Fujifilm Wako assay with a sensitivity of 79.4% and specificity of 88.3%. Previously, a study by Cento et al revealed that the single quantification of serum BDG using the Fujifilm Wako assay had a sensitivity of 56%, specificity of 87%, NPV of 85%, and PPV of 59% at the cutoff of 11 pg/mL in critically ill ICU and non-ICU patients [ 10 ]. Lowering the cutoff to 7.7 pg/mL, the sensitivity, specificity, NPV, and PPV were 56%, 87%, 85%, and 59%, respectively, similar to our findings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a study by Cento et al revealed that the single quantification of serum BDG using the Fujifilm Wako assay had a sensitivity of 56%, specificity of 87%, NPV of 85%, and PPV of 59% at the cutoff of 11 pg/mL in critically ill ICU and non-ICU patients [ 10 ]. Lowering the cutoff to 7.7 pg/mL, the sensitivity, specificity, NPV, and PPV were 56%, 87%, 85%, and 59%, respectively, similar to our findings [ 10 ]. Lower cutoffs for the Fujifilm Wako assay have been proposed previously.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, this biomarker has good negative predictive value when combined with clinical risk stratification and can therefore be used to rule out IFIs in clinical practice. 102 Another cell-wall marker of IFI is galactomannan (GM). GM is produced by Aspergillus spp, Penicillium spp and Histoplasma spp.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…and Pneumocystis jirovecii as well. Two assays are commercially available, 61,62 with no fixed cutoff values. 63 Across different studies, BDG has been shown to have a relatively high sensitivity (80%) and low specificity (55-60%).…”
Section: 3-β-d-glucanmentioning
confidence: 99%